International Cooperation Key to Addressing Prison Problems - español (2024)
The presence of transnational organized crime groups, along with other aspects in the prison context, and the conditions of infrastructure and equipment of social rehabilitation centers, which combine with overcrowding, causing overcrowding, are the main causes of the crisis in the prison sector, which has resulted in situations of extreme violence. The research carried out is framed in the study of the prison crisis as a global problem, with the objective of carrying out an analysis of the prison crisis in Ecuador and the intervention of international cooperation as a mechanism to contribute to matters of internal security, especially by supporting the fght against transnational organized crime, which has infltrated the centres of deprivation of liberty. Using the documentary analysis method, the study of the prison situation and the incidence of organized crime and the need to propose solutions in the feld of international cooperation have been attempted, particularly the most relevant aspects of the Assistance Program against Transnational Organized Crime Europe Latin America (EL PAcCTO) are described, trying to show the possible solutions to the crisis described. In conclusion, the relationship between different scourges such as corruption and the violation of human rights is shown as aspects that must be addressed.